Bacillus cereus cell response upon exposure to acid environment: toward the identification of potential biomarkers - DESRIAC, Noémie; Broussolle, Veronique; Postollec, Florence; Mathot, Anne-Gabrielle; Sohier, Daniele; Coroller, Louis; Leguerinel, Ivan (Frontiers in Microbiology, 2013)
Microorganisms are able to adapt to different environments and evolve rapidly, allowing them to cope with their new environments. Such adaptive response and associated protections towards other lethal stresses, is a crucial survival strategy for a wide spectrum of microorganisms, including food spoilage bacteria, pathogens and organisms used in functional food applications. The growing demand for minimal processed food yields to an increasing use of combination of hurdles or mild preservation factors in the food industry. A commonly used hurdle is low pH which allows the decrease in bacterial growth rate but also the inactivation of pathogens or spoilage microorganisms. Bacillus cereus is a well-known food-borne pathogen leading to economical and safety issues in food industry. Because survival mechanisms implemented will allow bacteria to cope with environmental changes, it is important to provide understanding of B. cereus stress response. Thus this review deals with the adaptive traits of B. cereus cells facing to acid stress conditions. The acid stress response of B. cereus could be divided into four groups (i) general stress response (ii) pH homeostasis, (iii) metabolic modifications and alkali production and (iv) secondary oxidative stress response. This current knowledge may be useful to understand how B. cereus cells may cope to acid environment such as encountered in food products and thus to find some molecular biomarkers of the bacterial behaviour. These biomarkers could be furthermore used to develop new microbial behaviour prediction tools which can provide insights into underlying molecular physiological states which govern the behaviour of microorganisms and thus opening the avenue toward the detection of stress adaptive behaviour at an early stage and the control of stress-induced resistance throughout the food chain.